The Growth of Barramundi (Lates Calcarifer) at the Marine and Brackish Water Aquaculture Center (BPBALP) Teluk Buo, Padang City, West Sumatra - Pangentasari, Dwinda; Harianto , Eko; Sumarsono, Teguh; Putinur, Putinur; Bareta, Ainun Rohmawati; Purnamasari , Tina; Nambela, Delima Sari; Lestari, Sekar Yunita (Department of Fisheries, Animal Science Faculty, Universitas Jambi., 2025)
Asian seabass (Lates calcarifer) is a promising aquaculture commodity at the UPTD Marine and Brackish Water Aquaculture Center (BPBALP) Teluk Buo, Padang City, due to its fast growth and high environmental adaptability. This study aimed to describe the growth techniques of Asian seabass cultured at BPBALP Teluk Buo and was conducted from July to September 2025 using a quantitative descriptive survey method. Growth performance was assessed through direct observation and measurement. The results showed an absolute weight gain of 123.6 g, length gain of 10.19 cm, a specific growth rate of 3.69%, feed efficiency of 68.5%, an FCR of 1.46, and a survival rate of 100%. Water quality remained within optimal ranges, with temperatures of 31–32 °C, pH 7, and salinity of 30–31 ppt.